MAP kinase activity supported by BRAFV600Emutation rather than gene amplification is associated with ETV1 expression in melanoma brain metastases - Birner, Peter; Capper, David; Deimling, Andreas von (Archives of dermatological research, 2014)
In primary melanoma, ETV1 transcription factor was suggested to be activated mainly by gene amplification and to promote tumor growth in cooperation with BRAFV600E. Aim of this study was to investigate ETV1 expression in human melanoma with a focus on brain metastases. We investigated ETV1 in 68 human melanoma brain metastases using FISH for ETV1 gene (located at chromosome 7p21) and centromere chromosome 7 and immunohistochemistry for ETV1, BRAFV600E, and ETV1/BRAF associated proteins pMSK1, pRSK1, pp38, pMEK1/2, MAPKAP kinase 2, CIC, HIF-1alpha and Ki-67. We further studied ETV1 copy number variations in 32 melanoma cell lines from primary and metastatic lesions using array CGH. The influence of the MAP kinase pathway activity on ETV1 mRNA and protein expression under BRAF wild-type and BRAFV600Econditions were determined in melanoma cell lines using qRT-PCR and Western Blot. No ETV1 high grade amplifications were observed in tissue samples, but low grade ETV1 gene amplifications were found in 7 (10.3 %) melanoma brain metastases. ETV1 protein expression in tissue samples (15 %) correlated with BRAFV600Estatus (p = 0.007) and HIF-1alpha expression (p = 0.049), but not with ETV1 gene dose. Application of the BRAFV600E-specific inhibitor vemurafenib and the BRAFV6ooE/V600K-inhibitor dabrafenib revealed predominant regulation of ETV-1 mRNA and protein via MAPK-pathway. ETV1 expression is a rare event in human melanoma and seems to be rather based on hyperactivation of MAPK signals, by BRAFV600Emutation, than on ETV1 gene amplification. Consequently, therapeutic inhibition of BRAF and the downstream MAPK pathway also down-regulates oncogenic ETV1 expression.